PROBIOTIC EFFECTS OF HEAT KILLED AND LIVE LACTOBACILLUS PLANTARUM ON PATHOGENIC BACTERIA AND HEK – 293 CELL LINES - PRATHIBA SANDEEP; P. SARAVANA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
The study was aimed to evaluate the impact of probiotic bacteria on HEK–293 kidney cell lines and action on pathogenic microbes. The heat killed and live L.plantarum cultures were treated on the HEK 293 cell lines and on pathogenic bacteria. The percentage of viability of the cell line was carried out by using Trypan blue dye exclusion method, by mtt assay it was proved that different concentrations of Heat killed and live strains of L.plantarum were treated on HEK-293 human embryonic kidney cells. The cell viability was not affected by the liver as well as heat killed strains. An antimicrobial assay was carried out to see the action on pathogens. The strain was most effective against gram positive Staphylococcus aureus and least effective against Shigella flexneri. The heat killed strain of L.plantarum is not harming the cell lines and works against pathogens.